KONTROL DIRI TERHADAP NOMOPHOBIA PADA REMAJA - Noorisa, Gina; Hariyono, Dyta Setiawati (Jurnal Bimbingan dan Konseling Pandohop, 2022)
Nowadays smartphones have become a basic necessity and a major part of the lifestyle of teenagers. The convenience and comfort provided by smartphones, will be a problem if used excessively which can have an impact on nomophobia. Nomophobia is a felling of fear that is because the smartphone is out of reach of its owner. This study aims to determine the influence of self-control on nomophobia in adolescents in Banjarmasin City. The subjects of this study were adolescents aged 17 to 21 years as many as 318 people. This research method uses quantitative. The sampling technidue in this study used purposive sampling. The data collection tools used are the self-control scale and the nomophobia scale which refers to the rating scale model. From the results of data analysis carried out with a simple linear regression test, a significance value of p= 0,034 (p<0,05) was obtained, meaning that there was a significant influence on self-control (X) on nomophobia (Y). Self-control in this study contributed 1,4% effectively to nomophobia.